Stewarding Shariah Finance: A Contemplative Reappraisal in Islamic Banking Across the ASEAN-6 Polity - Eogenie Lakilaki; Muhamad Zaky Ramadhan; Dwiki Ariefandri; Caroline Fitri Aurora; Qanita Triana; Wahyudi Ananta (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study examines the impact of four core Shariah compliant financing instruments, Mudharabah, Murabahah, Musharakah, and Ijarah, on the profitability of Islamic banks in the ASEAN-6 region, measured by Return on Assets (ROA). Using panel data from 20 Islamic banks across six countries (2020–2024), the study applies multiple regression analysis and classical assumption testing to ensure statistical robustness. Where contract disclosures were incomplete, data forecasting methods were applied. The findings indicate that Mudharabah, Murabahah, and Musharakah significantly enhance ROA, with Mudharabah showing the most pronounced effect, while Ijarah has no significant influence. These results support the relevance of Shariah Enterprise Theory, highlighting the role of ethical and participatory contracts in achieving profitability and Islamic economic justice. The study contributes novel insights by integrating Islamic worldview theory with empirical analysis across multiple jurisdictions. It also underscores the importance of incorporating ‘uqud murakkabah (hybrid contracts) and adopting digital innovations such as blockchain and smart contracts to improve transparency, mitigate risks, and strengthen Islamic financial infrastructure in alignment with Maqasid al-Shariah and sustainability objectives. Keywords: ASEAN-6; Islamic Banks; Profitability; Shariah Finance